Camrelizumab Plus Sorafenib Versus Sorafenib Monotherapy for Advanced Hepatocellular Carcinoma: A Retrospective Analysis - Liu, Qinqin; You, Nan; Li, Jing; Wu, Ke; Peng, Xuehui; Wang, Zheng; Wang, Liang; Zhu, Yinan; Zheng, Lu (Frontiers in Oncology, 2021)
Abstract Background: Hepatocellular carcinoma (HCC) is a highly aggressive malignancy with poor prognosis. Immunotherapy has gained great interest for various solid tumors due to its promising clinical efficacy. Targeted therapy also plays a crucial role in anticancer treatment. However, studies on the combination of immunotherapy and targeted therapy for advanced HCC are limited. Thus, the objective of this study was to investigate the efficacy and safety of camrelizumab combined with sorafenib in the treatment of advanced HCC. Methods: From January 2019 to January 2021, 100 consecutive patients with advanced HCC in our hospital were enrolled for this study. Patients were assigned into two groups: a combined -therapy group (camrelizumab + sorafenib) and a sorafenib -only group. Progression-free survival (PFS), overall survival (OS), treatment response, and relevant adverse effects (AEs) were evaluated and recorded. Results: Of a total of 100 patients, 35 received a combination of camrelizumab and sorafenib, and 65 were treated with sorafenib alone. After 1:1 propensity score matching (PSM), each group had 34 patients. The overall response rate (ORR) of the combined -therapy group was statistically significantly higher than that of the sorafenib -only group (before PSM, P = 0.037; after PSM, P = 0.010). However, there was no significant difference in disease control rate (DCR) between the two groups (before PSM, P = 0.695; after PSM, P = 1.000). Patients who received the combination therapy had significantly longer PFS than those who received the sorafenib monotherapy (before PSM, P = 0.041; after PSM, P = 0.043). However, the two groups exhibited comparable median OS (before PSM, P = 0.135; after PSM, P = 0.105). Although the combined - therapy group showed a higher incidence of AEs such as thrombocytopenia than the sorafenib -only group after PSM, most of these AEs were easily controlled after treatment. Conclusion: Camrelizumab plus sorafenib showed favorable efficacy and manageable toxicity for patients with advanced HCC. However, more prospective randomized trials are necessary to further verify the potential clinical benefits of this combination therapy.